Strengthening and Increasing MSME's Competitiveness in Supporting South Sulawesi Economic Growth - Idris, Muhammad; Echdar, Saban; Sabban, Yasrib Putranto; Sabban, Yusrab Ardianto (JURNAL MANAJEMEN BISNIS, 2022)
The objectives of this research for three years (2021-2023) are: Year I: (1) Mapping MSMEs in South Sulawesi which have prospects to become suppliers of large or export-oriented businesses, (2) Analyzing the effect of strengthening and increasing the competitiveness of MSMEs in sustaining South Sulawesi's economic growth; Year II: (1) Conducting guidance and education to MSMEs and coaching agencies at the levels provincial and district in strengthening and increasing competitiveness, (2) Reviewing and establishing strategies for strengthening and increasing MSMEs competitiveness; Year III: ( 1) Build a model for strengthening and increasing the competitiveness of MSMEs, and (6) Applying a model for strengthening and increasing the competitiveness of MSMEs so that unable to sustain the economic growth of South Sulawesi. Diladata collectionkukanthrough a survey with 120 respondents in four districts of the sample (Makassar, Pare-pare, Bantaeng and Bulukumba). Testing the hypothesis with the Structural Equation Model (SEM) through the help of Software SPSSVersion 25. The results revealed that strengthening and increasing the competitiveness of MSMEs had a positive and significant impact on supporting economic growth in South Sulawesi. For this reason, the goal of this research is to build a model of MSME competitiveness, it is important to realize it in the next research stage in 2022 and 2023. The implication of this research is to contribute ideas to the Government South Provincial Sulawesi in the form of a model for increasing the competitiveness of SMEs.